2021
DOI: 10.1371/journal.pone.0258919
|View full text |Cite
|
Sign up to set email alerts
|

Diet of a threatened endemic fox reveals variation in sandy beach resource use on California Channel Islands

Abstract: The coastal zone provides foraging opportunities for insular populations of terrestrial mammals, allowing for expanded habitat use, increased dietary breadth, and locally higher population densities. We examined the use of sandy beach resources by the threatened island fox (Urocyon littoralis) on the California Channel Islands using scat analysis, surveys of potential prey, beach habitat attributes, and stable isotope analysis. Consumption of beach invertebrates, primarily intertidal talitrid amphipods (Megalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…At the taxonomic level of class, island foxes harbored higher relative abundances of Gammaproteobacteria and Deltaproteobacteria compared to their island spotted skunks counterparts on both Santa Cruz and Santa Rosa Islands. Gammaproteobacteria have previously been linked to coastal amphipod species (Mengoni et al, 2013) similar to those preyed upon by island foxes (Page et al, 2021). They have also been associated with soil invertebrates such as earthworms (Zhang et al, 2021), which were recently introduced to the Channel Islands (Paudel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the taxonomic level of class, island foxes harbored higher relative abundances of Gammaproteobacteria and Deltaproteobacteria compared to their island spotted skunks counterparts on both Santa Cruz and Santa Rosa Islands. Gammaproteobacteria have previously been linked to coastal amphipod species (Mengoni et al, 2013) similar to those preyed upon by island foxes (Page et al, 2021). They have also been associated with soil invertebrates such as earthworms (Zhang et al, 2021), which were recently introduced to the Channel Islands (Paudel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It may also reflect evolutionary history, as Gammaproteobacteria have been isolated from other species within Canidae (Adams et al, 2021;DeCandia et al, 2021;Wetzels et al, 2021) The other class consistently more abundant in island foxes, Deltaproteobacteria, has previously been linked to marine environments (Liu & Häggblom, 2018), and may further reflect island fox foraging behavior on beaches (Page et al, 2021). While genus level results only included Deltaproteobacteria in the Santa Rosa Island comparisons, we were able to obtain finer scale taxonomic resolution, as genera Bilophila and Desulfovibrio were both significantly more abundant in island foxes compared to island spotted skunks on this island.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent work found that island fox populations exhibit a high degree of individualized diet specialization (Page et al 2021), suggesting that the quantity of seed dispersal services provided by individual foxes may be highly variable. Considering both the results of Page et al (2021) and our results, evidence suggests that island foxes may exhibit substantial individual-level variation in seed dispersal effectiveness. Future research examining potential endogenous and exogenous predictors of individual diet and germinability of digested seeds (e.g., individual social status, personality, or resource availability within the home range) may illuminate how individual-level variation in seed dispersal effectiveness by omnivorous mammals can contribute to spatial patterns in plant populations.…”
Section: Discussionmentioning
confidence: 99%
“…In finding that island foxes can be viable agents of seed dispersal for toyon, our results illustrate that variation in fox resource selection and space use may explain spatial patterns in seed movement and recruitment of fox-dispersed plant species on the Channel Islands. For example, recent work found that island fox populations exhibit a high degree of individualized diet specialization (Page et al 2021), suggesting that the quantity of seed dispersal services provided by individual foxes may be highly variable. Considering both the results of Page et al (2021) and our results, evidence suggests that island foxes may exhibit substantial individual-level variation in seed dispersal effectiveness.…”
Section: Future Directionsmentioning
confidence: 99%
“…Dugan et al ., 2003 ; Schlacher et al ., 2017 ), it logically follows that this marine‐derived material may enhance the breeding success and productivity of these birds. Such bottom‐up control of populations is also likely for other mobile animals that assimilate nutrients from invertebrates associated with beach‐cast wrack, such as lizards (Barrett et al ., 2005 ; Spiller et al ., 2010 ), rodents, foxes, and bears (Ricci et al ., 1998 ; Stapp & Polis, 2003 ; Fox et al ., 2014 ; Davidson et al ., 2021 ; Page et al ., 2021 ) as well as feral pigs (M.A. Mateo & J.E.…”
Section: The Current State Of Knowledgementioning
confidence: 99%